Identification and treatment of patients with high cardiovascular risk - I. V. Sergienko; S. Zh. Urazalina; V. V. Kukharchuk; Yu. A. Karpov (Кардиоваскулярная терапия и профилактика)
Aim. To perform an additional assessment of cardiovascular risk (CVR) levels in patients with low and moderate risk by SCORE scale (European Society of Hypertension/European Society of Cardiology, 2003, 2007), in order to identify the individuals with high CVR; to study the effectiveness of Liptonorm (atorvastatin) in lipid profile correction among these patients. Material and methods. At 12 policlinics (Moscow City, Western Autonomic City District), all patients visiting GPs were examined, with SCORE CVR levels assessed. The study included 600 patients with low and moderate risk. Additional examination at the Russian Cardiology Scientific and Clinical Centre took place one month later. All participants underwent duplex ultrasound of carotid arteries, with intima-media thickness (IMT) and atherosclerotic plaque (AP) assessment; computed sphygmography and automatic assessment of brachial-ankle pulse wave velocity (PWVba); blood assay and lipid profile assessment. Results. AP prevalence was 59 % (358 patients out of 600), while the prevalence of IMT increase >0,9 mm was only 5 % (28/600), which suggested a modest impact of IMT on total CVR. Pre-clinical arterial wall pathology was registered in 337 participants (56 %). The results obtained support the role of subclinical atherosclerosis as an independent risk factor (RF). Conclusion. Subclinical atherosclerosis diagnostics with duplex ultrasound of brachiocephalic arteries could be recommended for risk stratification.